SPE Annual Technical Conference and Exhibition 2010
DOI: 10.2118/135319-ms
|View full text |Cite
|
Sign up to set email alerts
|

Does the Presence of Natural Fractures Have an Impact on Production? A Case Study From the Middle Bakken Dolomite, North Dakota

Abstract: During the last 10 years, more than 2,000 horizontal wells have been drilled and completed in the Middle Bakken formation, which is sandwiched between the two Bakken organic-rich shales. Although most of the debate about this reservoir has centered on the lateral length, stimulation treatment, and the number of treatments, little work has been performed to explore the variations of rock properties and the effect of natural fractures along the 6,000 to 10,000 ft lateral lengths. Maintaining the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Gale, 2008;Mullen et al, 2010). Instead, we introduced here the bedding corridors as an addition to the natural fractures for optimizing hydrofracking design.…”
Section: Impact On Hydrofrackingmentioning
confidence: 99%
“…Gale, 2008;Mullen et al, 2010). Instead, we introduced here the bedding corridors as an addition to the natural fractures for optimizing hydrofracking design.…”
Section: Impact On Hydrofrackingmentioning
confidence: 99%
“…6). Mullen et al (2010) showed another fracture study for Bakken based on LWD micro-resistivity images. He reported the highest fracture density zone for Bakken in the well is as high as 0.69 fracture/ft or 1.45ft spacing in the sweet spot zones.…”
Section: Bakken Shalementioning
confidence: 99%
“…Recently, LWD electrical borehole images are used to design the optimum placement of the packers for multi-stage fracturing in the horizontal braches, (Mullen et al 2010). Recently, LWD electrical borehole images are used to design the optimum placement of the packers for multi-stage fracturing in the horizontal braches, (Mullen et al 2010).…”
Section: Lwd Horizontal Borehole Image Logging For Multi-stage Hydraumentioning
confidence: 99%
“…Several shale gas operators are also characterizing their lateral and horizontal boreholes with LWD images not only for reservoir navigation but also for better placement of the hydraulic fracturing stages, (Mullen et al 2010). These analyses are utilized to quantify the intrinsic rock anisotropy which can be used to derive anisotropic stress profiles.…”
Section: Introductionmentioning
confidence: 99%